Influence of mode mixity and loading rate on the fracture behaviour of crash resistant adhesives. (June 2020) - Borges, C.S.P.; Nunes, P.D.P.; Akhavan, A.; Marques, E.A.S.; Carbas, R.J.C.; Alfonso, L.; Silva, L.F.M.
Highlights: Determination of the impact strength and fracture envelopes of two epoxy adhesives. Mode II fracture toughness was studied using energy release rate (ENF) tests. Mixed mode studied with in-house developed apparatus, for static and impact loads. Strength increased for tensile and shear loading with increasing strain rate. Energy release rate increased for all loading modes with increasing strain rate. Abstract: The automotive industry, among other sectors, is progressively replacing traditional mechanical fasteners by adhesives. In this sector, passengers' safety is a priority. Thus, the behaviour of the automotive structure, including the adhesive joints within it, should be carefully studied. Adhesives are commonly subjected to loads that result from a combination of peel and shear, therefore, when studying their behaviour, both modes should be accounted for. The main aim of this work is the determination of the strength and fracture envelopes of two epoxy based crash-resistant adhesives at quasi-static conditions, intermediate speed and impact conditions. Mode I and tensile behaviour were already known thus, for the characterization of the strength envelope, thick adherend shear tests (TAST) were performed. For the establishment of the fracture envelope, mode II fracture toughness was studied using energy release rate (ENF) tests, and mixed mode was studied with two in-house developed apparatus, one for quasi-static conditions and a more robust one for intermediate speed and impact. Strength increased for tensile and shear loading with increasing strain rate. An increase was also recorded for the energy release rate at all mode-mixities studied, following a logarithmic trend.